THE USE OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN INFORMATICS LESSONS: OPPORTUNITIES, PRACTICE, AND PROSPECTS - Otepbergenov, Jetkerbay Sakbergenovich (SCIENCE and SOCIETY, 2026)
The article explores the potential and outcomes of utilizing Artificial Intelligence technologies in informatics lessons. AI-based adaptive environments personalize education by fostering algorithmic thinking and programming skills. Pilot projects and international experience demonstrate that AI enhances educational effectiveness, though challenges related to infrastructure and security are also noted.